The Liquid Smoke from Empty Oil Palm Bunches (Elaeis Guineensis Jacq.) as a Natural Fungicide and Its Ability to Inhibit the Growth of Colletotrichum sp. Fungus - Adam, Dini Hariyati; Hasibuan, Mila Nirmala Sari (Universitas Andalas, 2025)
The primary pest of red chili plants is anthracnose disease. Anthracnose is caused by the fungus Colletotrichum sp. Anthracnose is controlled with synthetic fungicides, but their long-term usage can harm the environment by leaving residues in the soil that are difficult to degrade, causing environmental degradation and a severe impact on the health of human. The goal of this study was to see how much potential liquid smoke had as a natural fungicide in preventing Colletotrichum sp. growth. It is recognized that liquid smoke emitted by empty oil palm bunches includes antioxidant compounds that function as antifeedants, contact poisons, and stomach poisons against plant pests. These compounds have the ability to act as natural fungicides, preventing the rise of Colletotrichum sp. The pyrolysis process produces liquid smoke at temperatures ranging from 350°C to 450°C. Total phenol and total acid content are determined from the obtained liquid smoke. The total phenol a material was identified using the well diffusion method, and the findings were 12.57%. Meanwhile, the maximum total acid content was found in liquid smoke from pyrolysis at 450oC (38.4 mg/L) with a volume of liquid smoke produced of 790mL. The ideal liquid smoke concentrations for limiting the increasing number of Colletotrichum sp. fungus are 20% and 30%, with average values of 4.28 and 7.73 mm, respectively. With a very strong inhibitory response category.